56.9k views
4 votes
Simplify the following expression: (5x2 + 3x + 4) − (2x2 − 6x + 3). If the final answer is written in the form Ax2 + Bx + C, what is the value of B?

Numerical Answers Expected!

2 Answers

1 vote
=5x2+3x+4-(2x2-6x+3)
=5x2+3x+4-2x2+6x-3
=3x2+9x+1
comparing it with Ax2+Bx+C we get B=9
User Anders Zommarin
by
5.3k points
3 votes
Combine like terms. remember to keep the signs.


5x² - 2x² = 3x²
3x - (-6x) = 3x + 6x = 9x
4 - (-3) = 7

3x² + 9x + 7 = Ax² + Bx + C

9 = B, because 9 is in the B's place

9 is your answer

hope this helps
User Milianoo
by
6.1k points